“Habonaron Do Bona”: Falsafah Nilai Masyarakat Simalungun dan Inspirasi Bagi Pendidikan anti Korupsi Di Indonesia - Yakobus Ndona; Liber Siagian; Pulumun Peterus Ginting (Al-Ulum, 2021)
The writing aims to reveal the wealth of values in the philosophy of habonaron do bona and find inspiration for anti-corruption education in Indonesia. In order to approach this problem, the research uses Max Scheler's axiological thinking as the primary reference. The study took data through interviews with Simalungun community leaders in the Seribu Dolok area, Simalungun Regency. The collected data were analyzed using philosophical hermeneutics: vertehen, translation, and interpretation. The interpretation movement uses Paul Recouer's hermeneutic circle pattern. The results of data analysis show that habonaron do bona has primary values that are structured like the structure of Max Scheler's values. Habonaron do Bona, both related to primary values and values education patterns, can be implemented for anti-corruption education in Indonesia.